Implementasi Putusan Mahkamah Konstitusi Nomor 123/PUU-VII/2009 terhadap Administrasi Kependudukan di Kabupaten Maluku Tengah dan Kabupaten Seram Bagian Barat - Stenly Ilela; Hendrik Salmon; Julista Mustamu (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research examines the disharmony between the body and its attachments in Law no. 40 of 2003 and its emphasis on population administration after Constitutional Court Decision no. 123/PUU-VII/2009. The method used is normative juridical with analysis of regulations and court decisions. The research results show that conflicting norms lead to open laws, dualism of authority and overlapping population data. The implementation of the Constitutional Court's decision has not been optimal because it has not been followed up through a judicial review. This condition has an impact on public services and certainty of people's domicile, so that regulatory harmonization is needed to guarantee legal security and the effectiveness of population administration.